DOXYCYCLINE BONE LABELING – IMPACT ON MRONJ TREATMENT - Vlad Daniel; Aureliana Caraiane; Adrian Creangă; Cristina Bartok-Nicolae (Romanian Journal of Oral Rehabilitation, 2022)
Background: Medication-related osteonecrosis of the jaws (MRONJ) represent a growing incidence pathology. Switching from bisphosphonate to denosumab treatment did not reduced the cases numbers, instead it increased the MRONJ incidence [1, 2]. Complete removal of necrotic bone is essential for wound healing [3]. Necrotic bone identification represent a challenge for a successful outcome. Main clinical criteria are the aspect of the bone and bleeding; imaging investigation commonly used are RMN and CT [4-7]. The aim of this study is to underline the value of doxycycline bone labeling in necrotic bone resection in MRONJ.